Pengaruh Rasio Keuangan Pada Financial Distress Perusahaan Ritel Yang Terdaftar di Bursa Efek Indonesia (BEI) - Agustini, Ni Wayan; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 26 No 1 (2019)DO - 10.24843/EJA.2019.v26.i01.p10, 2019)
This study aims to obtain empirical evidence regarding the effect of financial ratios, namely liquidity ratios, leverage, profitability, activity, and growth on retail financial distress companies listed on the Indonesia Stock Exchange (IDX). The study was conducted during the period 2013-2017 with a total sample of 75 observations selected by non-probability sampling method, namely purposive sampling. The data analysis technique used is logistic regression analysis. The results of the study prove that leverage ratios have a positive effect on financial distress. Profitability ratios and activity ratios have a negative effect on financial distress. The liquidity ratio and growth ratio have no effect on financial distress. Keywords : financial ratio, financial distress, interest coverage ratio